Growth arrest lines and intra-epiphyseal silhouettes: a case series - Ian W Kennedy; Greg J Irwin; James S Huntley (BMC Research Notes)
Abstract Background Growth arrest lines can develop within the skeleton after physiological stress or trauma. They are usually evident on radiographs as transverse lines in the metaphyses and have been used in fields from palaeontology to orthopaedics. This report consists of three cases, two of which describe growth arrest lines in an intra-epiphyseal site hitherto rarely documented, and a third demonstrating their clinical application. Case presentation Case 1 describes a 9-year-old who suffered a knee hyperflexion injury requiring anterior cruciate ligament and posterior cruciate ligament reattachments. She subsequently developed a marked distal femoral intra-epiphyseal arrest silhouette, as well as metaphyseal arrest lines in the femur, tibia and fibula. Case 2 describes an 8-year-old who sustained a tibial spine fracture and underwent open reduction and internal fixation. Subsequent imaging shows a further example of femoral intra-epiphyseal arrest silhouette as well as tibia and fibula metaphyseal arrest lines. Case 3 describes a 10-year-old who sustained a distal tibia fracture which was managed with open reduction and internal fixation. Subsequently the metaphyseal growth arrest line was parallel to the physis, suggesting no growth arrest (a danger with such a fracture). Conclusion This case series describes two examples of rarely described intra-epiphyseal growth arrest silhouettes and demonstrates the usefulness of arrest lines when assessing for growth plate damage.